Mangosteen Pericarp Extract Supplementation Boosts Antioxidant Status via Rebuilding Gut Microbiota to Attenuate Motor Deficit in 6-OHDA-Induced Parkinson's Disease - Bira Arumndari Nurrahma; Tu-Hsueh Yeh; Rong-Hong Hsieh; Shu-Ping Tsao; Chia-Wen Chen; Yen-Peng Lee; Chun-Hsu Pan; Hui-Yu Huang (MDPI AG, 2022)
Oxidative stress and gut dysbiosis have been known to precede Parkinson's disease (PD). An antioxidant-rich product, mangosteen pericarp (MP), has the ability to counterbalance excessive free radicals and the imbalanced gut microbiota composition, suggesting the MP's capacity to delay PD progression. In this study, we explored the effects of two doses of MP extract in a unilateral 6-hydroxydopamine (6-OHDA)-induced PD rat model. We revealed that the 8-week supplementation of a low dose (LMP) and a high dose of the MP extract (HMP) improved motor function, as observed in decreased contralateral rotation, improved time spent on rod, and higher dopamine binding transporter (DAT) in the substantia nigra pars compacta (SNc). The MP extract, especially the HMP, also increased antioxidant-related gene expressions, restored muscle mitochondrial function, and remodeled fecal microbiota composition, which were followed by reduced reactive oxygen species levels in brain and inflammation in plasma. Importantly, bacterial genera Sutterella, Rothia, and Aggregatibacter, which were negatively correlated with antioxidant gene expressions, decreased in the HMP group. It is imperative to note that in addition to directly acting as an antioxidant to reduce excessive free radicals, MP extract might also increase antioxidant state by rebuilding gut microbiota, thereby enhanced anti-inflammatory capacity and restored mitochondrial function to attenuate motor deficit in 6-OHDA-induced PD-like condition. All in all, MP extract is a potential candidate for auxiliary therapy for PD.